2001
DOI: 10.1161/01.atv.21.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Topographic Pattern of Progression of Coronary Calcification in Symptomatic Patients

Abstract: Abstract-Electron-beam CT may assess the progression of coronary atherosclerosis by visualizing changes in calcification. The present investigation analyzes (1) the rate of progression of calcification in symptomatic patients, (2) the topographic pattern, and (3) the influence of baseline plaque burden and risk factors. Progression of calcification during a mean (median) interval of 18 (15) months was measured in 102 symptomatic outpatients (aged 59Ϯ9 years, 80% male) with calcification. In 4 patient groups wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
73
1
12

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 24 publications
10
73
1
12
Order By: Relevance
“…4 -6 The presence and extent of coronary calcifications can be assessed noninvasively using fast CT techniques, such as electron beam tomography (EBT) 7,8 or multislice CT. 9,10 Several investigations have shown that the quantity of coronary calcium measured by CT progresses over time. 9,[11][12][13][14][15] Consistently, an increase in coronary calcium progression with increasing baseline calcium scores has been observed. 9,14,15 In the only investigation that included asymptomatic, randomly selected individuals, Maher et al 11 observed a 24% mean annual increase in the amount of coronary calcification when quantified using the Agatston score.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…4 -6 The presence and extent of coronary calcifications can be assessed noninvasively using fast CT techniques, such as electron beam tomography (EBT) 7,8 or multislice CT. 9,10 Several investigations have shown that the quantity of coronary calcium measured by CT progresses over time. 9,[11][12][13][14][15] Consistently, an increase in coronary calcium progression with increasing baseline calcium scores has been observed. 9,14,15 In the only investigation that included asymptomatic, randomly selected individuals, Maher et al 11 observed a 24% mean annual increase in the amount of coronary calcification when quantified using the Agatston score.…”
supporting
confidence: 55%
“…9,[11][12][13][14][15] Consistently, an increase in coronary calcium progression with increasing baseline calcium scores has been observed. 9,14,15 In the only investigation that included asymptomatic, randomly selected individuals, Maher et al 11 observed a 24% mean annual increase in the amount of coronary calcification when quantified using the Agatston score.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Indeed, evidence for regression of coronary calcification in humans has also been obtained. In a study of 102 symptomatic patients with coronary calcification currently being treated with standard medications, 15% of patients showed evidence of regression on the basis of electron beam computed tomography calcium scores measured at baseline and approximately 6 mo later (60).…”
Section: Can Vascular Calcification Be Controlled?mentioning
confidence: 99%